Pengaruh Ukuran Perusahaan, Leverage, Dan Sales Growth Terhadap Financial Distress (Studi Empiris Pada Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2015-2019) - Villy Nursayidah; Siti Asiyah; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study aims to determine and examine the effect of company size, leverage and sales growth on financial distress in food and beverage companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The population in this study were all food and beverage companies listed on the Indonesia Stock Exchange for the 2015-2019 period, as many as 30 companies. Meanwhile, the sample of this research was determined by purposive sampling method so that 6 samples were obtained. The type of data used is secondary data in the form of financial reports. The analytical method used is logistic regression analysis. The results of this study are simultaneously firm size, leverage and sales growth have an effect on financial distress. Meanwhile, the size of the company partially affects financial distress, and leverage and sales growth have no effect on financial distress. Keywords : Company Size, Leverage, Sales Growth, Financial Distress